Photoluminescence-Based Bioassay With Cysteamine-Capped TiO2 Nanoparticles for the Selective Recognition of N-Acyl Homoserine Lactones - Vasudevan, Sahana; Srinivasan, Parthasarathy; Neelakantan, Prasanna; Rayappan, John Bosco Balaguru; Solomon, Adline Princy (Frontiers in Bioengineering and Biotechnology, 2021)
Currently available diagnostic procedures for infections are laborious and time-consuming, resulting in a substantial financial burden by increasing morbidity, increased costs of hospitalization, and mortality. Therefore, innovative approaches to design diagnostic biomarkers are imperative to assist in the rapid and sensitive diagnosis of microbial infections. Acyl homoserine lactones (AHLs) are ubiquitous bacterial signaling molecules that are found to be significantly upregulated in infected sites. In this pioneering work, we have developed a simple photoluminescence-based assay using cysteamine-capped titanium oxide (TiO2) nanoparticles for AHL detection. The PL intensity variation of the oxygen defect state of TiO2 was used for the biosensing measurements. The bioassays were validated using two well-studied AHL molecules (C4-HSL and 3-oxo-C12 HSL) of an important human pathogen, Pseudomonas aeruginosa. The developed system has a maximum relative response of 98%. Furthermore, the efficacy of the system in simulated host urine using an artificial urine medium showed a linear detection range of 10–160 nM. Also, we confirmed the relative response and specificity of the system in detecting AHLs produced by P. aeruginosa in a temporal manner.